ANALYSIS OF STRATEGY WOMEN'S COOPERATIVE POTENTIAL DEVELOPMENT BASED ON HUMAN RESOURCES - Muttaqien, Fauzan; Rizki, Via Lailatur; Novy Fitria; Meilan, Ria Meilan (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2024)
This study is a qualitative study, aimed at analyzing the development of Human Resources in women's cooperatives in Lumajang Regency using Strength, Weakness, Opportunity, and Threats analysis, so that it becomes a consideration in determining the strategy for developing women's cooperative business. The target of this study was 54 women's cooperatives. The research used were primary and secondary data’s. The data collection technique used a questionnaire. The results of this study indicate that the strengths of women's cooperatives in Lumajang Regency are the level of knowledge and experience of cooperative managers, both with an average service period of 8 years. The level of education of the management is good, generally high school or equivalent. The internal capital and financial management of the cooperative is good, namely by paying attention to the principles of good and healthy governance. Women's Cooperatives strive to maximize their strengths as supporting factors for improving performance so that the weaknesses of Women's Cooperatives can be minimized. The results of the IFAS matrix analysis in the form of opportunity factors show that the potential for cooperative development due to the presence of a third party to establish partnerships through the support of information technology and government policies is very good. There is potential for business network cooperation between women's cooperatives at the regional and area levels, opportunities through government programs in the development of women's cooperatives and ease of licensing in the formation of new cooperatives as well as an increasingly open and conducive cross-sectoral business climate.